Can Young Children Draw What Does Not Exist?. (January 2020) - Harris, Paul L.
Research on children's drawing has focused primarily on the challenges they face in depicting reality on a two-dimensional surface. As they get older, their depictions become increasingly realistic. However, the development of drawing also reflects children's increasing ability to surmount another challenge, notably the constraints imposed by what they know about reality. In the course of development, children become increasingly capable of drawing creatures and objects that they have not observed and that do not exist. More specifically, they are able to imagine hybrids and other impossible entities and to depict what they imagine. By implication, the development of drawing involves two distinct trajectories: increased realism alongside a growing ability to escape the confines of known reality. Effectively, children gradually become capable of portraying the unreal as if it were real.